Single-Molecule Force Spectroscopy on the N2A Element of Titin: Effects of Phosphorylation and CARP - Lanzicher, Thomas; Zhou, Tiankun; Saripalli, Chandra; Keschrumrus, Vic; Smith III, John E.; Mayans, Olga; Sbaizero, Orfeo; Granzier, Henk (Frontiers in Physiology, 2020)
Titin is a large filamentous protein that forms a sarcomeric myofilament with a molecular spring region that develops force in stretched sarcomeres. The molecular spring has a complex make-up that includes the N2A element. This element largely consists of a 104-residue unique sequence (N2A-Us) flanked by immunoglobulin domains (I80 and I81). The N2A element is of interest because it assembles a signalosome with CARP (Cardiac Ankyrin Repeat Protein) as an important component; CARP both interacts with the N2A-Us and I81 and is highly upregulated in response to mechanical stress. The mechanical properties of the N2A element were studied using single-molecule force spectroscopy, including how these properties are affected by CARP and phosphorylation. Three protein constructs were made that consisted of 0, 1, or 2 N2A-Us elements with flanking I80 and I81 domains and with specific handles at their ends for study by atomic force microscopy (AFM). The N2A-Us behaved as an entropic spring with a persistence length (Lp) of ∼0.35 nm and contour length (Lc) of ∼39 nm. CARP increased the Lp of the N2A-Us and the unfolding force of the Ig domains; force clamp experiments showed that CARP reduced the Ig domain unfolding kinetics. These findings suggest that CARP might function as a molecular chaperone that protects I81 from unfolding when mechanical stress is high. The N2A-Us was found to be a PKA substrate, and phosphorylation was blocked by CARP. Mass spectrometry revealed a PKA phosphosite (Ser-9895 in NP_001254479.2) located at the border between the N2A-Us and I81. AFM studies showed that phosphorylation affected neither the Lp of the N2A-Us nor the Ig domain unfolding force (Funfold). Simulating the force-sarcomere length relation of a single titin molecule containing all spring elements showed that the compliance of the N2A-Us only slightly reduces passive force (1.4%) with an additional small reduction by CARP (0.3%). Thus, it is improbable that the compliance of the N2A element has a mechanical function per se. Instead, it is likely that this compliance has local effects on binding of signaling molecules and that it contributes thereby to strain- and phosphorylation- dependent mechano-signaling.